The microbiology of the Philippine fish sauce (patis) manufacture - Pelea, Ninfa Rodriguez
Following a commercial preparation procedure, fish sauce was prepared in a laboratory scale in triplicate vessels to study the fermentation process. The number of viable bacteria in the fish sauce was determined at regular intervals within one-month fermentation period. The results showed that for the three vessels the number of viable bacteria in fish sauce followed a similar trends in increase and decrease although the number per se was different. Changes in the number of viable bacteria in the fermenting fish sauce were correlated with changes in pH. For the three vessels, the estimated correlation coefficient between the two factors ranged from negligible to slight relations. The changes in the pH of the fish sauce within one-month fermentation period were limited within a narrow range (5.1 to 5.7) Correlation coefficient between the changes in logarithmic count of viable bacteria in the fermenting fish sauce and the changes in % titrable acidity (as lactic acid) was also determined. In all the vessels the correlation estimate between the two factors showed slight to negligible correlation except for the changes in a microaerophilic count in vessels A and C which showed substantial correlations. No particular microorganism was accounted for this observation. The morphological and biochemical characteristics of the bacteria isolated from fermenting fish sauce during the one-month fermentation period were studied in an attempt to identify and classify them. The moderate halophiles were separated from the extreme halophiles in a scheme proposed by Colwell et al (1979). Three stains of moderate and an unindentified gram-variable cocci. Halophilic strains belonging to the Genus Halobacterium and Halococcus were isolated from the fish sauce.